(untitled) (World Bulletin of Public Health, 2023)
The study was conducted to assess chronic non-puerperal uterine inversion mimicking complete uterine prolapsed. To carry out the study we presented a rare case of chronic uterine inversion mimicking a complete uterovaginal prolapse, a diagnostic dilemma requiring a high index of suspicious. Carrying out the study a case of a 34-year-old para 1 who presented with a prolonged history of vaginal bleeding, purulent vaginal discharge, and chronic pelvic pain of six months duration and a protruding vaginal mass of two months associated with urinary retention requiring urethral catheterization. Patient was initially and erroneously diagnosed as complete uterovaginal prolapsed. From the study it was observed that the uterine inversion is the invagination of the fundus of the uterus into the uterine cavity and through the cervix so that the uterus turns inside out. It can be acute (puerperal) or chronic(non-puerperal). The study concluded that chronic uterine inversion is a rare gynaecological condition. It was also concluded that the incidence is largely unknown and most available literature is based on case reports and that it posed a diagnostic dilemma and required a high index of suspicion. One of the recommendations made was that a good and thorough clinical evaluation and experienced sonographic report play a significant role in the early diagnosis and subsequent management of the patient